Freezing coagulating bath spinning preparation method of Al2O3-Aramid hybrid aerogel fiber with core-shell structure
The nanoaramid fiber is closely combined with the Al2O3 aerogel layer by the frozen solidification bath spinning method, which solves the problem of insufficient mechanical properties and high temperature resistance of aerogel fibers, and realizes the preparation of high-performance core-shell structure aerogel fibers , improving its stability and application potential.
Patent Information
- Application Number
- CN202411608811.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing aerogel fibers have shortcomings in terms of mechanical properties and high temperature resistance. In particular, the preparation method of core-shell structures has poor bonding effect inside and outside the core-shell, high thermal conductivity, poor mechanical properties and poor stability due to slow gel rate. The problem limits its large-scale production and application.
Using the frozen solidification bath spinning method, nanoaramid fibers are used as the core fibers and Al2O3 aerogel layer is used as the outer shell layer. The inner core shell is closely combined through immediate freezing effect and wet reaction to form high temperature resistance, low thermal conductivity, and mechanics. Excellent core-shell structure alumina-aramid hybrid aerogel fiber.
It significantly improves the stability of core-shell structure aerogel fiber, obtains good mechanical properties and thermal insulation properties, reduces synthesis difficulty, and expands its application prospects in more fields.
Smart Images

Figure CN119265720A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of aerogel fiber materials, and in particular relates to a method for preparing a core-shell structure Al2O3-Aramid hybrid aerogel fiber by freezing coagulation bath spinning. Background Art
[0002] Aerogel fiber is a continuous fiber material composed of aerogel particles, which combines the dual characteristics of aerogel and fiber materials. This unique structure gives aerogel fibers the characteristics of ultra-low density, ultra-high porosity and large specific surface area. Aerogel fibers have excellent thermal insulation properties, and their thermal insulation effect far exceeds that of ordinary fiber materials. They are considered to be the next generation of high-performance thermal insulation fibers for humans. In the past decade, researchers have developed a large number of aerogel fibers, including graphene, silica, cellulose, aramid and other types. These aerogel fibers show broad application prospects in the fields of thermal insulation, flame retardancy, electromagnetic shielding, etc.
[0003] However, the research and development of aerogel fibers also faces some challenges, such as the difficulty in achieving both low thermal conductivity and high strength, insufficient high temperature resistance, and poor weavability. For example, aramid aerogel fibers have insufficient temperature resistance, and alumina aerogel fibers have poor mechanical properties. To address these issues, researchers are constantly exploring new preparation methods and processes to improve the mechanical properties and high temperature resistance of aerogel fibers. In particular, for the preparation of core-shell aerogel fibers, traditional methods such as coaxial spinning, impregnation, and coating have problems such as poor bonding between the core and the shell, high thermal conductivity due to slow gelation rate, poor mechanical properties, and poor stability, which severely limit their large-scale production and application.
[0004] In view of this, it is particularly urgent and important to accelerate the research and development of aerogel fiber technology with high temperature resistance, low thermal conductivity and excellent mechanical properties. In the future, aerogel fibers are expected to be widely used in more fields. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a core-shell structured Al2O3-Aramid hybrid aerogel fiber by freezing coagulation bath spinning, using nano-aramid fiber as the "core fiber" and an Al2O3 aerogel layer as the outer shell layer, and utilizing the instant freezing effect of the freezing coagulation bath and the chemical reaction of the wet reaction spinning to tightly combine the inner core and the outer shell together to obtain a new core-shell structured alumina-aramid hybrid aerogel fiber with high temperature resistance, low thermal conductivity and excellent mechanical properties.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a core-shell structure Al2O3-Aramid hybrid aerogel fiber by freezing coagulation bath spinning, comprising the following steps:
[0008] (1) adding 2-8 mm aramid short-cut fibers to N-methylpyrrolidone and soaking them for 10-14 hours, ultrasonically treating them for 20-40 minutes to remove impurities and sizing agents on the fiber surface, and then washing them with anhydrous ethanol and pure water in turn and drying them in a constant temperature oven to obtain completely dried and dispersed aramid nanofibers;
[0009] (2) adding completely dried and broken up aramid nanofibers and potassium salt into dimethyl sulfoxide to prepare a 0.5-8 wt % aramid nanofiber dispersion; the aramid nanofiber dispersion is sealed and stored away from light to prevent sedimentation;
[0010] (3) preparing a coagulation bath, adding aluminum chloride hexahydrate to a mixed solution of ethanol and water, stirring, and continuing the reaction for 6 to 10 hours after the aluminum chloride hexahydrate is completely dissolved, and then dropping a dilute hydrochloric acid solution, stirring and reacting to obtain an aluminum chloride aluminum sol, wherein the mass ratio of the aluminum chloride hexahydrate, ethanol, water, and dilute hydrochloric acid solution is 1:6 to 20:6:2;
[0011] (4) uniformly injecting the aramid nanofiber dispersion into a -20 to -80°C frozen coagulation bath aluminum sol, performing multiphase frozen wet reaction spinning to obtain cryogel fibers, soaking the fibers in the frozen coagulation bath aluminum sol for 20 to 26 hours, waiting for gel aging, and obtaining gel-aged cryogel fibers;
[0012] (6) The gel-aged cryogel fibers are repeatedly washed with pure water to obtain wet gel fibers, and then the wet gel fibers are placed in a displacement solvent for solvent displacement, and then freeze-dried at -50 to -60°C and 0.03 to 0.06 MPa for 24 to 48 hours to finally obtain Al2O3-Aramid hybrid aerogel fibers.
[0013] Furthermore, the potassium salt is powdered potassium hydroxide or potassium tert-butoxide.
[0014] Furthermore, when the mass concentration of the aramid nanofiber dispersion is ≤2wt%, the potassium salt is powdered potassium hydroxide, and the specific preparation method of the aramid nanofiber dispersion is: adding the completely dried and broken up aramid nanofibers and powdered potassium hydroxide to dimethyl sulfoxide to obtain a mixed solution, the mass ratio of the aramid nanofibers to the potassium hydroxide is 1:1-2, and the mixed solution is vigorously stirred for 7 days under nitrogen protection, the aramid nanofibers are gradually dissolved, and the solution changes from colorless to dark red viscous liquid and is sealed and stored away from light, thereby preparing the aramid nanofiber dispersion.
[0015] Furthermore, when the mass concentration of the aramid nanofiber dispersion is >2wt%, the potassium salt is potassium tert-butoxide, and the specific preparation method of the aramid nanofiber dispersion is: add completely dried and broken up aramid chopped fibers and potassium tert-butoxide in a mass ratio of 1:1 to 1.5 to dimethyl sulfoxide, stir evenly, add a proton additive with the same mass as the aramid chopped fibers, and continue stirring under nitrogen protection for 3 to 8 hours until the sample is evenly reacted and dissolved to obtain an aramid nanofiber dispersion.
[0016] Furthermore, the mass ratio of aluminum chloride hexahydrate, ethanol, water and dilute hydrochloric acid solution in step (3) is 1:6 to 14:6:2.
[0017] Furthermore, the proton auxiliary agent is one or more of anhydrous methanol, ethanol and water.
[0018] Furthermore, in the spinning parameters, when the mass concentration of the aramid nanofiber dispersion is ≤2wt%, the extrusion speed is 10-20ml / min, and the spinning needle diameter is 19-22G; when the mass concentration of the aramid nanofiber dispersion is >2wt%, the extrusion speed is 2-5mL / min, and the spinning needle diameter is 13-16G. The selection of the extrusion speed and needle diameter depends on the concentration of the dispersion and the required fiber diameter, ensuring uniform extrusion of the fiber and proper precipitation in the coagulation bath.
[0019] Furthermore, the replacement solvent in step (6) includes one or more of water, ethanol, cyclohexane, n-hexane, and 25% tert-butanol aqueous solution.
[0020] Furthermore, the concentration of the dilute hydrochloric acid solution in step (3) is 1 mol / L.
[0021] In the aerogel fiber spinning process, high-speed gel fiberization of the spinning solution is the prerequisite for the preparation of aerogel fibers, and the synthesis of a spinning solution with a high gel rate is the key to the preparation of aerogel fibers with a core-shell structure. Traditional sol materials have problems such as the coexistence of hydrolysis and polycondensation, and the gel rate is generally slow, which cannot meet the needs of aerogel fiber spinning. Reaction spinning can make the dispersion gel quickly through the rapid reaction between the coagulation bath and the spinning solution when the spinning solution contacts the coagulation bath, greatly shortening the gel time, and providing conditions for the preparation of aerogel fibers with large flux. At the same time, the freezing coagulation bath transforms the gel fiber into a frozen gel fiber, which can maintain the fiber shape while making the aramid nanofiber dispersion and the aluminum sol coagulation bath react more fully. At room temperature, the dispersion combines before the acid proton, the intermolecular hydrogen bond force is weak, and the binding with aluminum ions is also weak. The viscosity of the aluminum sol increases at -20 to -80°C. During the reaction process, the aluminum sol with a higher viscosity has better adhesion with the aramid nanofiber dispersion and a more complete reaction.
[0022] In view of this, the present invention uses aramid nanofibers as raw materials to successfully prepare a highly reactive aramid nanofiber dispersion, and uses aluminum chloride hexahydrate as raw materials to successfully prepare an aluminum sol coagulation bath. The aluminum sol coagulation bath is placed in a -20 to -80°C refrigerator to make the aluminum sol coagulation bath in a supercooled state. After the nanofiber dispersion enters the coagulation bath, on the one hand, the nanofiber dispersion is re-protonated and assembled, and the aramid nanowires are rapidly instable and cross-linked. On the other hand, the supercooled coagulation bath can rapidly coagulate the aramid spinning solution, ensuring the high-speed molding of the gel fiber and the effective combination with the shell. Based on the two-phase gel and freezing reaction, the high-speed gelation of the spinning solution is ensured while forming a gel fiber with a core-shell structure. Aramid nanofibers are used as "core fibers" and their advantages such as high mechanical strength, high concentration of liquid crystal state and high drawing tolerance are utilized to ensure the weavability of the composite fiber material. The Al2O3 aerogel layer is used as the outer shell layer, giving full play to its ultra-low thermal conductivity and high temperature resistance advantages. Combined with the construction of the above-mentioned freezing-two-phase solution reaction mechanism, the effective generation of Al2O3-Aramid hybrid aerogel fibers is ensured, and the skeleton strength of Al2O3-Aramid hybrid aerogel fibers is effectively improved, ensuring the stability of the structure. It should be pointed out that the two-phase gel reaction strategy used in the present invention forms a composite gel transition phase at the interface of the Al2O3-Aramid two phases, ensuring the close connection between the core layer and the shell layer, and improving the stability of the core-shell structure Al2O3-Aramid hybrid aerogel fibers.
[0023] The advantages and positive effects of the present invention are:
[0024] The present invention uses aramid nanofiber spinning solution and aluminum sol freezing coagulation bath solution, combines freezing spinning strategy to produce two-phase reaction and freezing double forming in the spinning process, and performs high-speed spinning of aerogel fibers, which significantly reduces the difficulty of synthesizing aerogel fibers with core-shell structure and improves the stability of the core-shell structure. The prepared core-shell structure Al2O3-Aramid hybrid aerogel fibers have good mechanical properties and thermal insulation properties, and the preparation method of the present invention has good expansion capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a macroscopic photograph of the Al2O3-Aramid aerogel fiber prepared in Example 1;
[0026] Figure 2 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Example 1 at a magnification of 1150 times;
[0027] Figure 3 This is a macroscopic photograph of the Al2O3-Aramid aerogel fiber prepared in Example 2;
[0028] Figure 4 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Example 2 at a magnification of 760 times;
[0029] Figure 5 This is a 330-fold magnified SEM image of the Al2O3-Aramid aerogel fiber prepared in Example 3;
[0030] Figure 6 This is a SEM image of the Aramid aerogel fiber prepared in Comparative Example 1 at a magnification of 250 times;
[0031] Figure 7 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 2 at a magnification of 190 times;
[0032] Figure 8 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 3 at a magnification of 410 times;
[0033] Fig. 9 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 4 at a magnification of 215 times;
[0034] Fig.10 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 5, magnified 295 times;
[0035] Fig.11 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 6, magnified 280 times. DETAILED DESCRIPTION
[0036] In order to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings. In the case of no conflict, the features in the case can be combined with each other. The raw materials used in the following examples are all commercially available analytically pure raw materials.
[0037] Example 1
[0038] A method for preparing a core-shell structure Al2O3-Aramid hybrid aerogel fiber by freezing coagulation bath spinning, comprising the following steps:
[0039] (1) Preparation of aramid nanofiber dispersion: 10 g of 5 mm long aramid short-cut fibers were soaked in 50 g of N-methylpyrrolidone for 12 h, and then ultrasonically treated for 30 min to remove impurities and sizing agents on the fiber surface. The fibers were then washed with anhydrous ethanol and pure water three times in sequence and dried in a constant temperature oven at 80 °C for 5 h to obtain completely dried and dispersed aramid nanofibers.
[0040] (2) adding 10.0 g of completely dried and broken aramid nanofibers and 20.0 g of potassium hydroxide to dimethyl sulfoxide, and stirring for 7 days under nitrogen protection to prepare a 2.0 wt% aramid nanofiber dispersion;
[0041] (3) Weighing 20 g of aluminum chloride hexahydrate with an electronic balance, adding it to a hydroalcoholic solution of 280 g of ethanol and 120 g of water, stirring it thoroughly to hydrolyze it, and after the aluminum chloride hexahydrate is completely dissolved, adding 40 g of 1 mol / L dilute hydrochloric acid to promote hydrolysis to obtain aluminum chloride aluminum sol;
[0042] (4) placing aluminum chloride hexahydrate in an ultra-low temperature refrigerator at -80°C to freeze, obtaining a supercooled solidification bath, extruding the aramid nanofiber dispersion into the supercooled solidification bath through a pump-controlled syringe, the extrusion rate is 10 ml / min, using a needle with a diameter of 19G, the aramid nanofiber dispersion forms cryogel fibers in the supercooled solidification bath, and then gelling in the freezing solidification bath for 24 hours, waiting for gel aging, and obtaining gel-aged cryogel fibers;
[0043] (5) The gel-aged cryogel fibers were washed with water and ethanol in turn to remove residual dimethyl sulfoxide and the coagulation bath, and then transferred to a 25wt% tert-butyl alcohol aqueous solution for solvent replacement for 48 hours, with the replacement solvent replaced every 12 hours. Subsequently, they were placed in an ultra-low temperature refrigerator at -80°C for 24 hours, and vacuum freeze-dried at 0.05MPa and -50°C for 24 hours to obtain Al2O3-Aramid hybrid aerogel fibers with a core-shell structure.
[0044] The macroscopic photograph of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 1 is shown in FIG. Figure 1 As shown, the scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 1 is as follows Figure 2 shown.
[0045] Example 2
[0046] A method for preparing a core-shell structure Al2O3-Aramid hybrid aerogel fiber by freezing coagulation bath spinning, comprising the following steps:
[0047] (1) The preparation of aramid nanofibers is the same as in Example 1;
[0048] (2) Add 8.0 g of aramid nanofibers and 8.0 g of potassium tert-butoxide to 76 g of refined DMSO and stir rapidly for 10 minutes. Then, add 8.0 g of anhydrous methanol in 4 batches within 1 hour and continue stirring for 8 hours until the sample is uniform, thereby obtaining an 8 wt% aramid nanofiber dispersion.
[0049] (3) Weigh 20 g of aluminum chloride hexahydrate using an electronic balance and add it to a hydroalcoholic solution of 280 g and 120 g of water. Stir thoroughly to hydrolyze the aluminum chloride hexahydrate. After the aluminum chloride hexahydrate is completely dissolved, add 40 g of 1 mol / L dilute hydrochloric acid to promote hydrolysis and obtain aluminum chloride sol.
[0050] (4) placing the aluminum chloride sol in an ultra-low temperature refrigerator at -80°C and freezing it, and extruding the aramid nanofiber dispersion into a supercooled solidification bath through a pump-controlled syringe at an extrusion rate of 3 ml / min, using a needle with a diameter of 16G, the aramid nanofiber dispersion forms cryogel fibers in the supercooled solidification bath, and then gelling in the freezing solidification bath for 24 hours, waiting for gel aging, and obtaining gel-aged cryogel fibers;
[0051] (5) The gel-aged cryogel fibers were washed with water and ethanol in turn, and then transferred to a 25wt% tert-butyl alcohol aqueous solution for solvent replacement for 48 hours, with the replacement solvent replaced every 12 hours. They were then placed in a -80°C freezer for 24 hours, and vacuum freeze-dried at 0.05MPa and -50°C for 24 hours. Al2O3-Aramid hybrid aerogel fibers with a core-shell structure were obtained.
[0052] The macroscopic photograph of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 2 is shown in FIG. Figure 3 As shown, the scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 2 is as follows Figure 4 shown.
[0053] Example 3
[0054] The only difference from implementation 1 is that in step (4), the aluminum chloride aluminum sol is placed in an ultra-low temperature -40°C refrigerator for freezing.
[0055] The scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 3 is as follows: Figure 5 shown.
[0056] Comparative Example 1
[0057] A method for preparing Aramid aerogel fibers by freezing coagulation bath spinning. The preparation method is the same as that of Example 1, except that the only difference is step (3): converting the coagulation bath liquid into a mixed solution of ethanol and water.
[0058] The scanning electron microscope image of the aerogel fiber-based thermal insulation material prepared in Comparative Example 1 is as follows: Figure 6 shown.
[0059] Comparative Example 2
[0060] A method for preparing Al2O3-Aramid hybrid aerogel fiber by wet reaction spinning, the preparation method is the same as that of Example 1, and the difference is only in step (4) and step (5): placing aluminum chloride aluminum sol at room temperature, and extruding aramid nanofiber dispersion into a coagulation bath by a pump-controlled syringe, the extrusion speed is 3ml / min, and a needle with a diameter of 16G is used to obtain wet gel fiber; the wet gel fiber is washed with water and ethanol in sequence, and then transferred to a 25wt% tert-butyl alcohol aqueous solution for solvent replacement for 48h, and the replacement solvent is changed every 12h. Then it is placed in a -80℃ freezer for 24h, and vacuum freeze-dried at 0.05MPa and -50℃ for 24h. That is, Al2O3-Aramid hybrid aerogel fiber with a core-shell structure is obtained.
[0061] The scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Comparative Example 2 is as follows: Figure 7 shown.
[0062] Comparative Example 3
[0063] The only difference from Comparative Example 2 is that in step (4), the aluminum chloride sol is placed at 10°C.
[0064] The scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Comparative Example 3 is as follows: Figure 8 shown.
[0065] Comparative Example 4
[0066] The only difference from Comparative Example 2 is that in step (4), the aluminum chloride sol is placed at 0°C.
[0067] The scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Comparative Example 4 is as follows: Fig. 9 shown.
[0068] Comparative Example 5
[0069] The only difference from Example 1 is step (4), in which the aluminum chloride hexahydrate sol is placed in a -10°C refrigerator and frozen.
[0070] The scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Comparative Example 5 is as follows: Fig.10 shown.
[0071] Comparative Example 6
[0072] The only difference from Example 1 is that in step (4), the aluminum chloride hexahydrate sol is placed in a -90°C refrigerator and frozen.
[0073] The scanning electron microscope image of the Al2O3-Aramid hybrid aerogel fiber prepared in Comparative Example 6 is as follows: Fig.11 shown.
[0074] Evaluation and characterization
[0075] Figure 1 This is a macroscopic photograph of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 1. Figure 2 This is a SEM image of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 1, magnified 1150 times. Figure 3 This is a macroscopic photograph of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 2. Figure 4 This is a SEM image of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 2, magnified 760 times. Figure 5 This is a 330-fold magnified SEM image of the Al2O3-Aramid hybrid aerogel fiber prepared in Example 3. It can be seen that the shell layer and the core layer of the core-shell Al2O3-Aramid hybrid aerogel fiber prepared in the present invention are tightly combined, and the core layer is densely organized and evenly distributed. This stable shell structure enables the Al2O3-Aramid hybrid aerogel fiber to have good mechanical properties, low thermal conductivity and high temperature resistance.
[0076] Figure 6 This is a 250-fold magnified SEM image of the Aramid aerogel fiber prepared in Comparative Example 1. It can be seen that the core-shell structure cannot be formed using a conventional coagulation bath; Figure 7 The SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 2 is magnified 190 times. The gelation speed of the room temperature coagulation bath is slower than that of the frozen coagulation bath, and the internal and external bonding is not good, and the surface is wrinkled and detached. The frozen coagulation bath can achieve high-speed spinning and good molding of the aerogel fiber. The inner and outer layers are tightly combined by intermolecular forces. At the same time, the Al2O3-Aramid hybrid aerogel fiber with a core-shell structure has better high temperature resistance than the Aramid aerogel fiber. The addition of alumina components improves the high temperature resistance of the outer layer of the fiber, thereby improving the overall high temperature resistance of the fiber and broadening its scope of use in high temperature extreme environments.
[0077] Figure 8 This is a 410-fold magnified SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 3. Fig. 9 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 4, magnified 215 times; Fig.10 This is a SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 5, magnified 295 times. Fig.11This is a 280-magnified SEM image of the Al2O3-Aramid aerogel fiber prepared in Comparative Example 6. It can be seen from Examples 8 to 10 that as the coagulation bath temperature gradually decreases from 10°C, 0°C, and -10°C, the bonding between the core layer and the shell layer becomes better and better. The core-shell fiber prepared at low temperature has a more stable and complete structure than that at room temperature, but the overall structure is not as good as the shell structure of the embodiment. The core-shell aerogel fiber prepared at -90°C has a tight bond between the outer shell and the inner core, but the interior has collapsed. This is because the freezing coagulation bath with too low a temperature is not conducive to the formation of the porous network structure of the inner core layer.
[0078] The tensile breaking strength of the fiber was tested by an Instron universal testing machine, the sample was set to 1 cm long, the tensile rate was 1 mm / min, and the maximum tensile breaking strength of the fiber was measured. The thermal conductivity was measured by a thermal insulation material thermal conductivity tester. The data are shown in Table 1.
[0079] Table 1
[0080] name Mechanical properties (MPa) <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> Example 1 4.0 0.032 Example 2 4.2 0.030 Example 3 4.1 0.033 Comparative Example 1 3.2 0.038 Comparative Example 2 3.3 0.038 Comparative Example 3 3.5 0.037 Comparative Example 4 3.6 0.037 Comparative Example 5 3.5 0.038 Comparative Example 6 3.6 0.039
[0081] It can be seen from Table 1 that the mechanical properties of the aerogel fiber prepared in the embodiment are higher than those of the aerogel fiber prepared in the comparative example. This is because the sol-gel process is the result of the combined action of the dual mechanisms of coagulation bath and freezing. The spinning solution is squeezed into the freezing coagulation bath to form a more ordered oriented structure under low temperature conditions of -20 to -80°C, thereby improving the mechanical and physical properties of the aerogel fiber. The thermal conductivity of the embodiment is lower than that of the comparative example. Due to the addition of the low thermal conductivity alumina aerogel layer of the outer shell, and the formation of a composite gel transition phase at the interface of the Al2O3-Aramid two phases, the close connection between the core layer and the shell layer is ensured, and the structure is more stable, ensuring that the Al2O3-Aramid aerogel fiber has a lower thermal conductivity and better thermal insulation effect. At the same time, due to the difference in coagulation bath temperature, the degree of bonding between the inner core and the outer shell of the aerogel fiber is different, and the thermal conductivity is slightly different, but the overall fluctuation is not large.
[0082] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a core-shell structure Al2O3-Aramid hybrid aerogel fiber by freezing coagulation bath spinning, characterized in that: The steps include: (1) adding 2-8 mm aramid short-cut fibers to N-methylpyrrolidone and soaking them for 10-14 hours, ultrasonically treating them for 20-40 minutes, washing them with anhydrous ethanol and pure water in turn, and drying them in a constant temperature oven to obtain completely dried and dispersed aramid nanofibers; (2) adding completely dried and dispersed aramid nanofibers and potassium salt into dimethyl sulfoxide to prepare a 0.5-8 wt % aramid nanofiber dispersion; (3) adding aluminum chloride hexahydrate to a mixed solution of ethanol and water, stirring, and continuing the reaction for 6 to 10 hours after the aluminum chloride hexahydrate is completely dissolved, and then dropping a dilute hydrochloric acid solution, stirring and reacting to obtain an aluminum chloride aluminum sol, wherein the mass ratio of the aluminum chloride hexahydrate, ethanol, water, and dilute hydrochloric acid solution is 1:6 to 20:6:2; (4) uniformly injecting the aramid nanofiber dispersion into a -20 to -80°C frozen coagulation bath aluminum sol, performing multiphase frozen wet reaction spinning to obtain cryogel fibers, soaking the fibers in the frozen coagulation bath aluminum sol for 20 to 26 hours, waiting for gel aging, and obtaining gel-aged cryogel fibers; (5) The gel-aged cryogel fibers were repeatedly washed with water and ethanol, placed in a replacement solvent for solvent replacement, and then placed in an ultra-low temperature refrigerator at -80°C for 8 to 24 hours of freezing treatment, and then freeze-dried at -40 to -60°C and 0.05 MPa for 24 to 48 hours to finally obtain Al2O3-Aramid hybrid aerogel fibers.
2. The preparation method according to claim 1, characterized in that: The potassium salt is powdered potassium hydroxide or potassium tert-butoxide.
3. The preparation method according to claim 2, characterized in that: When the mass concentration of the aramid nanofiber dispersion is ≤2wt%, the potassium salt is powdered potassium hydroxide. The specific preparation method of the aramid nanofiber dispersion is: adding completely dried and broken up aramid nanofibers and powdered potassium hydroxide to dimethyl sulfoxide to obtain a mixed solution, wherein the mass ratio of the aramid nanofibers to the potassium hydroxide is 1:1-2, and the mixed solution is vigorously stirred for 5-8 days under nitrogen protection, the aramid nanofibers are gradually dissolved, and the solution is sealed and stored away from light after changing from colorless to dark red viscous liquid, thereby preparing the aramid nanofiber dispersion.
4. The preparation method according to claim 2, characterized in that: When the mass concentration of the aramid nanofiber dispersion is greater than 2wt%, the potassium salt is potassium tert-butoxide, and the specific preparation method of the aramid nanofiber dispersion is as follows: adding completely dried and broken up aramid chopped fibers and potassium tert-butoxide in a mass ratio of 1:1 to 1.5 to dimethyl sulfoxide, stirring, adding a proton additive having the same mass as the aramid chopped fibers, and continuing to stir under nitrogen protection for 3 to 8 hours until the sample is evenly reacted and dissolved to obtain the aramid nanofiber dispersion.
5. The preparation method according to claim 1, characterized in that: The mass ratio of aluminum chloride hexahydrate, ethanol, water and dilute hydrochloric acid solution in step (3) is 1:6 to 14:6:
2.
6. The preparation method according to claim 4, characterized in that: The proton auxiliary agent is one or more of anhydrous methanol, ethanol and water.
7. The preparation method according to claim 1, characterized in that: Among the spinning parameters, when the mass concentration of the aramid nanofiber dispersion is ≤2wt%, the extrusion speed is 10-20ml / min, and the spinning needle diameter is 19-22G; when the mass concentration of the aramid nanofiber dispersion is >2wt%, the extrusion speed is 2-5mL / min, and the spinning needle size is 13-16G.
8. The preparation method according to claim 1, characterized in that: The replacement solvent in step (6) includes one or more of water, ethanol, cyclohexane, n-hexane, and 25% tert-butanol aqueous solution.
Citation Information
Patent Citations
Aluminum oxide ceramic aerogel fibers and sol-gel spinning preparation method thereof
CN111574204A
High-toughness aramid aerogel fiber as well as preparation method and application thereof
CN115073803A
Method for preparing heat-resistant fiber composite aluminum oxide-silicon dioxide hybrid aerogel
CN116199493A
Preparation method and application of aerogel fiber
CN117779230A
Spinning of fibers and films from particulate dispersions
FR1169567A